Perbandingan antara Penginapan Syariah dan Non-Syariah di Kabupaten Pacitan - Erma Dwi Astari; Khoirun Nisak (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Lodging is a business that provides services for someone to stay or rest for a certain period. It is none other than Sharia-based accommodation; the main goal is to provide a place for guests to rest and provide services, providing facilities at prices that suit their needs. The difference is that Sharia itself includes rules about how Muslims should live, as well as implementing Sharia principles in accordance with the DSN-MUI fatwa. The research compares services, facilities, and prices in sharia and non-syariah accommodation in Pacitan Regency. Apart from that, another aim is to find out whether the accommodation is by the reviews given by visitors with services and facilities according to the price offered. Values ​​or ratings with almost the same class can influence visitors' interest in purchasing lodging. The Sharia lodgings and non-sharia lodgings studied experienced differences in ratings with almost the same service qualifications, facilities, and prices. The method used in this research is a qualitative descriptive approach. Data collection methods use observation, interview and documentation techniques. This research indicates that Sharia accommodation and non-sharia accommodation represent two different approaches in the hotel or lodging industry. Sharia accommodation establishes its identity through Sharia principles with services that comply with Islamic law. In contrast, non-Shariah accommodation focuses on comfort and practicality without highlighting religious values ​​and frees visitors from staying overnight.